Pemanfaatan Asap Cair Bambu Terhadap Kualitas Ikan Segar Selama Masa Penyimpanan - Hewul, Sernince Rambu (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2018)
Fish is easily damaged food because it contains high protein and water content up to 80%, and high nutrient content so that fish is a good medium for the growth of bacteria and other microorganisms. Therefore the handling of fish that necessary to be done in order to maintain this quality of fish and extend the self life of fish without reduce the nutritional percentage with maximum. Handling fresh fish with distribution of liquid smoke can reduce the deterioration speed of fish quality,  foremost in reduction microbe activity and chemistry reaction such as decomposition of protein. The purpose of this study was to determine the concentration of liquid smoke and storage time in fresh fish. This research uses experimental method with variables 0-48 hours with different concentrations. The main tools used are pyrolysis reactor and distillation process, with bamboo raw material. The analyzes used the GC-MS tool, and the parameters measured included: phenol content, rendement, pH value and benzopirene levels. The results of this study indicate that the use of bamboo liquid smoke that is more effective and optimal to be applied to fresh fish is with a concentration of 4% on a saving of 12 hours with phenol content of 3.45% and pH value 3.52.